2004
DOI: 10.1111/j.0014-3820.2004.tb00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Reptile Color Variation and the Evolution of the McIr Gene

Abstract: Abstract. The wealth of information on the genetics of pigmentation and the clear fitness consequences of many pigmentation phenotypes provide an opportunity to study the molecular basis of an ecologically important trait. The melanocortin-1 receptor (Mc1r) is responsible for intraspecific color variation in mammals and birds. Here, we study the molecular evolution of Mc1r and investigate its role in adaptive intraspecific color differences in reptiles. We sequenced the complete Mc1r locus in seven phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 64 publications
4
85
0
Order By: Relevance
“…Colour variation of the dorsal body surface has often been interpreted as an adaptation for crypsis (Rosenblum, 2005), and experimental studies have shown that substrate matching strongly influences avian predation rates (Kaufman, 1974;Hoekstra, 2006). Colour polymorphism in reptiles may be caused by genetic variability, for example, variation in the Mc1r gene (Rosenblum, Hoekstra & Nachman, 2004), or may be a consequence of an ontogenetic change in response to environmental stimuli (Dunn, 1982;Rosenblum, 2005). found major inconsistencies between morphological taxa and mtDNA clades of the T. graeca complex and reported a strong correlation between substrate and tortoise colour in some regions.…”
Section: Discussionmentioning
confidence: 99%
“…Colour variation of the dorsal body surface has often been interpreted as an adaptation for crypsis (Rosenblum, 2005), and experimental studies have shown that substrate matching strongly influences avian predation rates (Kaufman, 1974;Hoekstra, 2006). Colour polymorphism in reptiles may be caused by genetic variability, for example, variation in the Mc1r gene (Rosenblum, Hoekstra & Nachman, 2004), or may be a consequence of an ontogenetic change in response to environmental stimuli (Dunn, 1982;Rosenblum, 2005). found major inconsistencies between morphological taxa and mtDNA clades of the T. graeca complex and reported a strong correlation between substrate and tortoise colour in some regions.…”
Section: Discussionmentioning
confidence: 99%
“…Although variation in colour pattern in populations of the MRC could reflect an underlying level of biodiversity within this group, but reptile coloration has long been studied as an example of adaptive evolution (e.g. Cott, 1940;Rosenblum et al, 2004). So far there has not been a comprehensive study performed on the adaptive nature of intra-and interpopulation variation in colour pattern of the MRC.…”
Section: Introductionmentioning
confidence: 99%
“…A number of well known case studies have demonstrated links between ecology, phenotypic variation, and underlying genetic mechanisms [e.g., Drosophila and Heliconius, reviewed in Kronforst et al (2012)]. For example, ecological selection for matching background color in pocket mice living on dark lava rock compared to light sand (Nachman et al 2003) and similarly for skin coloration of White Sands lizards on different substrates (Rosenblum et al 2004) has driven genetic changes underlying pigmentation variation between populations and species. Research on pigmentation has increasingly turned its focus to the evolution and maintenance of integrated phenotypes.…”
Section: Introductionmentioning
confidence: 99%